2008
DOI: 10.1021/ja711063f
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Epoxide

Abstract: Oxidation of graphite may be carried out by reaction with meta-chloroperoxybenzoic acid to yield graphite epoxide. Scanning tunneling microscopy (STM) showed that the functionalization occurs at the edges rather than on the basal plane of the graphite. Quantification of the epoxide content is possible through the deepoxidation reaction using MeReO3/PPh3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 18 publications
5
49
0
Order By: Relevance
“…Since the entire basal plane will not be functionalised, the edges allow for attachment of PEI but in very low concentrations. This conclusion was confirmed by synthesising graphite epoxide, [24] and then reacting it with PEI. Previous studies [24] have shown that when graphite epoxide is synthesised the oxidation takes place on the edges of the sheet and not on the basal plane.…”
Section: Pei-gicmentioning
confidence: 64%
See 1 more Smart Citation
“…Since the entire basal plane will not be functionalised, the edges allow for attachment of PEI but in very low concentrations. This conclusion was confirmed by synthesising graphite epoxide, [24] and then reacting it with PEI. Previous studies [24] have shown that when graphite epoxide is synthesised the oxidation takes place on the edges of the sheet and not on the basal plane.…”
Section: Pei-gicmentioning
confidence: 64%
“…This conclusion was confirmed by synthesising graphite epoxide, [24] and then reacting it with PEI. Previous studies [24] have shown that when graphite epoxide is synthesised the oxidation takes place on the edges of the sheet and not on the basal plane. The product of reactions with PEI showed a similar degree of functionalisation by TGA to PEI-GICs, indicating that PEI was only added to the edges and not the basal plane.…”
Section: Pei-gicmentioning
confidence: 64%
“…Surprisingly, the epoxidation did not give rise to a higher portion of singly bonded oxygen (either epoxide or phenol/hydroxyl) in the oNPC sample, in comparison with the pristine NPC sample. It has been known that stable graphite epoxide was synthesized from epoxidation of graphite by using a similar approach [26]. However, sine the C-C bonds are the more reactive sites relative to C=C in sucrose-derived carbon, those fresh epoxides could be preferentially anchored on dangling C-C bonds.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is still suggested more efforts could be devoted to understanding the roles of epoxides on graphitic carbons in electrochemical storage of monovalent cations, considering the unique physicochemical properties of epoxides and the difficulty in the synthesis of highly porous graphite epoxide [17,20,26]. believed that all the TFSI − anions were washed away from the OCV electrode.…”
Section: (E)mentioning
confidence: 99%
See 1 more Smart Citation